2020
DOI: 10.3390/w12040985
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Groundwater Spring Potential in Karst Aquifer System Using Novel Ensemble Bivariate and Multivariate Models

Abstract: Groundwater is an important natural resource in arid and semi-arid environments, where discharge from karst springs is utilized as the principal water supply for human use. The occurrence of karst springs over large areas is often poorly documented, and interpolation strategies are often utilized to map the distribution and discharge potential of springs. This study develops a novel method to delineate karst spring zones on the basis of various hydrogeological factors. A case study of the Bojnourd Region, Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 149 publications
(151 reference statements)
0
24
0
Order By: Relevance
“…and Bagging [53]. Such ensemble models also have been used in many other fields, for example groundwater potential mapping [46,54], gully erosion distribution modeling [55], and flood prediction [56].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…and Bagging [53]. Such ensemble models also have been used in many other fields, for example groundwater potential mapping [46,54], gully erosion distribution modeling [55], and flood prediction [56].…”
Section: Study Areamentioning
confidence: 99%
“…Recent advances in data processing techniques have shown that the performance of machine learning methods can be further improved, and their limitations alleviated, using ensemble learning methods [40][41][42][43][44], which were first introduced in the early 1990s [45,46]. Ensemble methods have outperformed single model methods in terms of accuracy and robustness [40].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ensemble and hybrid machine learning techniques have provided promising results and have been widely used around the world in recent years [17,18,22,52,56,98,99]. Their base classifiers have good predictive ability and have been successful in predicting landslide-prone areas.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction accuracy of landslide susceptibility models depends on the geographical region, landslide conditioning factors (LCF), sample size, and on hyper parameter tuning [18,99]. As yet, there is no consensus as to which models are most appropriate for specific regions, hence it is necessary to use a variety of methods in each study area to determine the method with the highest predictive power.…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerability assessments have been conducted for natural disasters other than earthquakes, including floods [22][23][24][25][26], landslides [27][28][29][30][31][32][33][34], gully erosion [35][36][37][38][39], and groundwater contamination [40][41][42][43][44]. Some studies have compared the performance of various methodologies, including probabilistic techniques such as frequency ratio (FR) models [22,27,43], statistical techniques such as LR-based models [22,27,28,32,34,38,[40][41][42][43], and machine learning algorithms such as decision tree (DT) [24,26,28,29,31,34,38,39,[42][43][44], random forest (RF) …”
Section: Introductionmentioning
confidence: 99%